Ensino colaborativo entre professoras de atendimento educacional especializado e da sala regular : uma análise sobre os saberes resultantes dessa interação na prática profissional - Seleghim, Claudia Elisa (Universidade Federal de São Carlos, 2023)
This study starts from the perspective of the importance of Collaborative Teaching as a proposal for cooperation between teachers from the Specialized Educational Service (AEE) and the regular classroom, with a view to including target students in Special Education (PAEE). In defense of this premise, and seeking clues to prove it, this research aimed to investigate the practice of an AEE teacher in collaboration with three teachers from common classes of regular education at a municipal public school in the interior of São Paulo, with the aim of analyzing which knowledge is mobilized in their actions, and reflect on the extent to which they can contribute to the process of continued training of the teachers involved. This is a qualitative and autoethnographic research, based on the researcher's perspective and immersion with three regular class teachers, working in elementary school I (1st to 5th year). To develop the study, initially, an analysis of academic research on the topic was carried out; Secondly, the researcher's practice was analyzed, covering four reflective moments: 1) description of the practice (what do I do?); 2) inform (what does this mean?); 3) confront (how did I become this way? How did I end up acting this way?); and 4) rebuild (how can I do it differently?); Finally, questionnaires were administered to the participating teachers, containing closed and open questions, aiming to achieve the proposed objectives. The theoretical framework was chosen based on a survey of research and authors in the area, focusing on the field of epistemology of practice, teaching knowledge and Special Education - with emphasis on issues focused on collaborative teaching and Specialized Educational Service. The analyzes carried out on the literature in the area indicated that the collaboration process requires training, dialogue, reflection and planning, on the part of everyone involved, so that the actions are carried out and fulfill their roles, especially, providing access and the necessary conditions for student learning. With empirical research, in triangulation with other data, it was possible to verify what the literature had already revealed, with an emphasis on understanding the need for inclusive practices in schools, and creating actions based on effective collaboration between the AEE teacher and the regular classroom teacher. It was also found that teaching knowledge was developed in parallel to the application and analysis of this research, itself consisting of the final product. Therefore, the pertinence and relevance of carrying out this work stands out in terms of its contribution to strengthening practice and teaching, enabling students to experience consistent and articulated educational processes, and, not least, future research in the area of Special Education and Inclusive.
Collaborative teaching between special education support teachers and regular classroom teachers: an analysis of the knowledge resulting from this interaction in professional practice
Keywords: Saberes docentes; Ensino Colaborativo; Atendimento educacional especializado; Teaching knowledge; Collaborative teaching; Specialized educational service; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL